A spatially-enabled Internet application to support information access. - Snorri Guðjón Sigurðsson (2009)
This document describes the work on the development of a spatially-enabled Internet application to support information access about the University of Akureyri. The system is a interface to a database that holds nodes, ways, relations and tags. Hopefully this project will be useful to the University of Akureyri to support information access about the University both for employees and students.